2020
DOI: 10.1136/jclinpath-2020-206879
|View full text |Cite
|
Sign up to set email alerts
|

Fatal pulmonary fibrosis: a post-COVID-19 autopsy case

Abstract: There is growing evidence of histopathological changes in autopsied individuals infected with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2); however, data on histopathological changes in autopsied patients with eradicated COVID-19 are limited. We performed an autopsy on a Caucasian female in her 80s, who died due to severe, bilateral pulmonary fibrosis after eliminated SARS-CoV-2 infection. In addition, CT scans from 2 months before infection and from 6 days prior to death were compared. Compari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
72
0
7

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(83 citation statements)
references
References 20 publications
(18 reference statements)
2
72
0
7
Order By: Relevance
“…A previously reported case (80 years female subject) by Schwensen et al that had recovered from COVID‐19 and she had no history of pulmonary illness, however, she was suffering from bilateral lung fibrosis as a result of COVID‐19 which leads to her death 20 . Regarding cardiac involvement, it was reported that some COVID‐19 subjects suffered from myocarditis as a complication of COVID‐19 which was consistent with the finding of this study 21 .…”
Section: Discussionsupporting
confidence: 89%
“…A previously reported case (80 years female subject) by Schwensen et al that had recovered from COVID‐19 and she had no history of pulmonary illness, however, she was suffering from bilateral lung fibrosis as a result of COVID‐19 which leads to her death 20 . Regarding cardiac involvement, it was reported that some COVID‐19 subjects suffered from myocarditis as a complication of COVID‐19 which was consistent with the finding of this study 21 .…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, although COVID-19 is still recent, it is possible to infer that interstitial fibrosing could be an important future sequel in recovered patients. As revealed by Schwensen H F [51], destruction of lung parenchyma with fibrous organization and beginning of immature fibroblasts proliferation, was reported in an autopsy performed after clinical cure of COVID-19, indicating interstitial fibrosing as an important histomorphological sequel of this new disease.…”
Section: Pathologymentioning
confidence: 84%
“…Since it has been reported in the literature that equal than other coronaviruses are responsible for producing pulmonary fibrosis [ 38 , 39 , 40 , 41 ], and that this has also been recognized as a sequel to acute respiratory distress syndrome (ARDS). Also, dyspnea related with COVID-19 can be associated with heart problems [ 42 , 43 ], so its origin should be investigated, and recovered patients should be followed up, since the extent of the complications is still unknown [ 44 ].…”
Section: Discussionmentioning
confidence: 99%